Auto-organização de partículas coloidais magnéticas - Domingos, Jorge Luiz Coelho (2013)
Colloidal systems, typically consisting of mesoscopic particles in a microscopic solvent, can be stabilized so that the colloids crystallize into ordered structures. The predictions of such phases is a relevant problem for technological applications, but it offers difficulties in the case of numerical studies, which are usually associated with the large number of metastable states, which in turn is sensible to the considered theoretical model. Another determining factor is the geometry of the colloid itself. In this dissertation we study the influence of two very important features of self-assembly in colloidal systems, namely: i ) the interparticle interaction, which in this work we consider to be of the magnetic dipolar type; ii) the shape of the colloids, which we assume to be anisotropic, unlike what is usually considered in the literature. Magnetic particles have been chosen because they are widely used in several applications such as magnetic fluids and biomedicine. We use molecular dynamics and Monte Carlo technique in this work in order to obtain the ground state configurations. On the first part of this work, we study the ground state configurations of a two-dimensional binary system of circular magnetic particles in a parabolic trap. We set the magnitude of the magnetic dipole moment of one group of particles, while the magnitude of the dipole moment of the other group is changed. The system presents a spatial separation between the two types of particles so that those ones with higher dipole moment stays on the outer part of the clusters, indicating that the repulsive part of the interaction overcomes the attractive one. We apply a uniform magnetic field parallel to the plane of confinement and we study the minimum energy configurations as a function of the strength of this field. In some cases, we find a non-monotonic behavior of the magnetization (alignment) of the system as a function of the magnetic field strength. On the second part of this work, we study the self-assembly of a two-dimensional system of magnetic particles with anisotropic shape (rod-like) as a function of the size of them. We notice that the increase of the packing fraction, at low temperature, favors the ordering (alignment) of the system. In general, we notice three phases, one phase composed of clusters, a disordered phase and a nematic ordered phase. Finally, we study dependence of the equilibrium structures on temperature, through a correlation function associated to the global alignment of magnetic moments.